Generating Optimized Test Case from UML Diagram Using Meta-Heuristic Algorithm - Preeti; Goyal, Rohit (International Journal of Computer Sciences and Engineering, 2019)
Properly tested software is better in quality then the software tested using a poor approach or not tested. Increasing size and complexity of software makes manual testing process a time, cost and resource consuming task. Automating the testing process can improve software development process. The unified modeling language (UML) is the most widely used language to describe the analysis and designs of object-oriented software. Test cases can be derived from UML models more efficiently. In our work, we propose a novel approach for automatic test case generation from the combination of UML state chart, sequence and activity diagrams. In our approach, we first draw the UML state chart, sequence and activity diagrams. Then convert these diagrams to graphs and generate a combined graph. This graph is then used to generate test paths. We have integrated meta-heuristic algorithm i.e. Genetic Algorithm (GA) for this purpose and found fruitful results.